Współpraca rodziny i szkoły - o lepszą jakość relacji rodzice - nauczyciele - Danuta Opozda (Nicolaus Copernicus University in Toruń, 2009)
The article deals with an issue involving the role of cooperation between the family   and the school with a detailed discussion upon the relationship between the parent and   the teacher. The quality of this bond describes the area, the motivation and aims of this   type of the cooperation of basic educational environment: the family and the school.   The starting point is of this discussion is the adoption of statute and duties of parents for   upbringing. It implies to take the precedence over parents in the process of upbringing   and the rule of assistance o other people or institutions over them. There is also a remark   made in the article about the difficulties in the relationship which reveals itself in the   asymmetry and andgragocentrism which points to a sharp dominance of adults with high   superiority of a teacher and minimization or exclusion of child's participation. There   main postulates in the area of shaping the proper relationships are: caring about proper   atmosphere, authentic dialogue and appreciation of the same aims subsequent to cyclicalphase   model of development of a child. The collaboration between the parents and the   school in not the phenomenon "all or nothing" and there should be no dichotomization.   It is a fact which can be assigned in the category of independent multi-value which is   dependent form many individualized conditions.